Răspuns:
a = 19
Explicație pas cu pas:
[tex]2 \times [(2 \times a - 36) \div 2 + 20] - 32 = 10 \\ [/tex]
[tex]2 \times [(2 \times a - 36) \div 2 + 20] = 10 + 32 \\ [/tex]
[tex]2 \times [(2 \times a - 36) \div 2 + 20] = 42[/tex]
[tex](2 \times a - 36) \div 2 + 20 = 42 \div 2[/tex]
[tex](2 \times a - 36) \div 2 + 20 = 21[/tex]
[tex](2 \times a - 36) \div 2 = 21 - 20[/tex]
[tex](2 \times a - 36) \div 2 = 1[/tex]
[tex]2 \times a - 36 = 1 \times 2[/tex]
[tex]2 \times a - 36 = 2[/tex]
[tex]2 \times a = 2 + 36[/tex]
[tex]2 \times a = 38[/tex]
[tex]a = 38 \div 2 = > a = 19[/tex]